2011
DOI: 10.1111/j.1365-2966.2011.18746.x
|View full text |Cite
|
Sign up to set email alerts
|

Polarimetric study of transiting extrasolar planets

Abstract: We present the results of modelling the polarization produced during planetary transits in the systems HD 189733, TrES‐3, Wasp‐4 and Wasp‐25, using the Monte Carlo method. Polarization maxima at the limb are calculated to be ∼0.022 per cent for HD 189733 with stellar polarization according to Chandrasekhar. The polarization for the system HD 189733 of ∼0.022 per cent is close to that previously published, although this was attributed to scattering of starlight, rather than produced in transit. Using three‐dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Obviously, the latter approximation is too rough to predict the observational values of transit polarization. Thus, Frantseva et al (2012), assuming solar limb polarization for HD 189733, obtained the polarization that is different by almost two orders of magnitude as compared to Kostogryz et al (2011), showing the importance of knowing the intrinsic stellar polarization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the latter approximation is too rough to predict the observational values of transit polarization. Thus, Frantseva et al (2012), assuming solar limb polarization for HD 189733, obtained the polarization that is different by almost two orders of magnitude as compared to Kostogryz et al (2011), showing the importance of knowing the intrinsic stellar polarization.…”
Section: Introductionmentioning
confidence: 99%
“…They also explored the cases of K-M-T dwarfs with a simplified limb polarization approximation and suggested that in favorable situations ground-based polarimetry should be able to detect Earth-like planets orbiting these stars. Kostogryz et al (2011) using the same Monte Carlo technique, simulated the transit polarization for several objects with high planet-to-star radii ratio. For the TrES-3, WASP-4 and WASP-25 systems with G spectral type host stars the modelled solar limb polarization (Trujillo Bueno & Shchukina 2009) was chosen, while for one of the brightest transit exoplanetary system HD 189733 (K spectral type) pure scattering atmosphere approximation (Chandrasekhar 1960) was applied.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lucas et al (2012) failed to detect polarimetric variations in two other promising systems hosting hot-Jupiters, 55 Cnc and τ Boo, reaching accuracy limits of 5 × 10 −6 . Kostogryz et al (2011) attribute the detection of Berdyugina et al (2011) to (stellar) polarisation caused at the limb during planetary transit, but the correct interpretation remains unclear.…”
Section: Polarised Light From An Earth-like Planet In the White Dwarfmentioning
confidence: 99%
“…Despite not yet having been exploited, great hope is placed in the polarimetry capabilities of current and future telescopes as powerful tools for detecting and characterizing exoplanets (see Seager et al 2000;Saar & Seager 2003;Stam 2003Stam , 2008Stam et al 2004;Snik & Keller 2013). Previous works in this field involve the modeling of stellar polarization during planetary transits (Carciofi & Magalhães 2005;Kostogryz et al 2011Kostogryz et al , 2015Wiktorowicz & Laughlin 2014;Sengupta 2016), the modeling of light curves and polarization of starlight reflected signals in the visible range of Earth-like planets (Stam 2008;Karalidi et al 2012;Rossi & Stam 2017) and giant Jupiter-like planets (Seager et al 2000; A&A 618, A162 (2018) Stam et al 2004), as well as the modeling of exoplanetary atmospheres in the infrared (De Kok et al 2011;Marley & Sengupta 2011), which demonstrated the usefulness of direct observations for exoplanet characterization. More recently, Bott et al (2016) reported linear polarization observations of the hot Jupiter system HD 189733, and Ginski et al (2018) announced the detection of planetary thermal radiation that is polarized upon reflection by circumstellar dust.…”
Section: Introductionmentioning
confidence: 99%